Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Sure, let's go through each part step-by-step in detail.
### Part 1: Perform the Indicated Operations
#### (i) [tex]\(-1 + 3 - 6\)[/tex]
1. Start with [tex]\(-1\)[/tex].
2. Add [tex]\(3\)[/tex]: [tex]\(-1 + 3 = 2\)[/tex].
3. Subtract [tex]\(6\)[/tex]: [tex]\(2 - 6 = -4\)[/tex].
So, [tex]\(-1 + 3 - 6 = -4\)[/tex].
#### (ii) [tex]\(-4 + (2 \times -3)\)[/tex]
1. Start with [tex]\(2 \times -3\)[/tex].
2. Calculate the multiplication: [tex]\(2 \times -3 = -6\)[/tex].
3. Now, add [tex]\(-4\)[/tex]: [tex]\(-4 + (-6) = -4 - 6 = -10\)[/tex].
So, [tex]\(-4 + (2 \times -3) = -10\)[/tex].
### Part 2: Perform the Fraction Operations
#### (i) [tex]\(2 \frac{1}{5} + \frac{3}{10}\)[/tex]
1. Convert [tex]\(2 \frac{1}{5}\)[/tex] to an improper fraction.
- [tex]\(2 \frac{1}{5}\)[/tex] is the same as [tex]\(2 + \frac{1}{5}\)[/tex], which is [tex]\(2.2\)[/tex].
- In improper fraction form, [tex]\(2.2\)[/tex] is [tex]\(\frac{11}{5}\)[/tex] (since [tex]\(2 \frac{1}{5} = \frac{10}{5} + \frac{1}{5} = \frac{11}{5}\)[/tex]).
2. Add [tex]\(\frac{11}{5}\)[/tex] and [tex]\(\frac{3}{10}\)[/tex].
- Convert [tex]\(\frac{11}{5}\)[/tex] to have a common denominator with [tex]\(\frac{3}{10}\)[/tex].
- [tex]\(\frac{11}{5} = \frac{22}{10}\)[/tex] (by multiplying both numerator and denominator by 2).
- Now add: [tex]\(\frac{22}{10} + \frac{3}{10} = \frac{22 + 3}{10} = \frac{25}{10}\)[/tex].
- Simplify [tex]\(\frac{25}{10}\)[/tex] to [tex]\(2.5\)[/tex].
So, [tex]\(2 \frac{1}{5} + \frac{3}{10} = 2.5\)[/tex].
#### (ii) [tex]\(\frac{7}{8} \times \frac{2}{3} - \frac{1}{4}\)[/tex]
1. Multiply [tex]\(\frac{7}{8}\)[/tex] by [tex]\(\frac{2}{3}\)[/tex].
- [tex]\(\frac{7}{8} \times \frac{2}{3} = \frac{7 \times 2}{8 \times 3} = \frac{14}{24}\)[/tex].
- Simplify [tex]\(\frac{14}{24}\)[/tex]:
- The greatest common divisor (GCD) of 14 and 24 is 2.
- [tex]\(\frac{14}{24} = \frac{7}{12}\)[/tex] when divided by GCD.
2. Subtract [tex]\(\frac{1}{4}\)[/tex] from [tex]\(\frac{7}{12}\)[/tex].
- Convert [tex]\(\frac{1}{4}\)[/tex] to have a common denominator with [tex]\(\frac{7}{12}\)[/tex].
- [tex]\(\frac{1}{4} = \frac{3}{12}\)[/tex] (by multiplying both numerator and denominator by 3).
- Now subtract: [tex]\(\frac{7}{12} - \frac{3}{12} = \frac{7 - 3}{12} = \frac{4}{12}\)[/tex].
- Simplify [tex]\(\frac{4}{12}\)[/tex]:
- The GCD of 4 and 12 is 4.
- [tex]\(\frac{4}{12} = \frac{1}{3}\)[/tex].
So, [tex]\(\frac{7}{8} \times \frac{2}{3} - \frac{1}{4} = 0.33333333333333337\)[/tex] (or [tex]\(\frac{1}{3}\)[/tex] approximately).
### Summary
1. (i) [tex]\(-1 + 3 - 6 = -4\)[/tex]
(ii) [tex]\(-4 + (2 \times -3) = -10\)[/tex]
2. (i) [tex]\(2 \frac{1}{5} + \frac{3}{10} = 2.5\)[/tex]
(ii) [tex]\(\frac{7}{8} \times \frac{2}{3} - \frac{1}{4} = 0.33333333333333337\)[/tex]
### Part 1: Perform the Indicated Operations
#### (i) [tex]\(-1 + 3 - 6\)[/tex]
1. Start with [tex]\(-1\)[/tex].
2. Add [tex]\(3\)[/tex]: [tex]\(-1 + 3 = 2\)[/tex].
3. Subtract [tex]\(6\)[/tex]: [tex]\(2 - 6 = -4\)[/tex].
So, [tex]\(-1 + 3 - 6 = -4\)[/tex].
#### (ii) [tex]\(-4 + (2 \times -3)\)[/tex]
1. Start with [tex]\(2 \times -3\)[/tex].
2. Calculate the multiplication: [tex]\(2 \times -3 = -6\)[/tex].
3. Now, add [tex]\(-4\)[/tex]: [tex]\(-4 + (-6) = -4 - 6 = -10\)[/tex].
So, [tex]\(-4 + (2 \times -3) = -10\)[/tex].
### Part 2: Perform the Fraction Operations
#### (i) [tex]\(2 \frac{1}{5} + \frac{3}{10}\)[/tex]
1. Convert [tex]\(2 \frac{1}{5}\)[/tex] to an improper fraction.
- [tex]\(2 \frac{1}{5}\)[/tex] is the same as [tex]\(2 + \frac{1}{5}\)[/tex], which is [tex]\(2.2\)[/tex].
- In improper fraction form, [tex]\(2.2\)[/tex] is [tex]\(\frac{11}{5}\)[/tex] (since [tex]\(2 \frac{1}{5} = \frac{10}{5} + \frac{1}{5} = \frac{11}{5}\)[/tex]).
2. Add [tex]\(\frac{11}{5}\)[/tex] and [tex]\(\frac{3}{10}\)[/tex].
- Convert [tex]\(\frac{11}{5}\)[/tex] to have a common denominator with [tex]\(\frac{3}{10}\)[/tex].
- [tex]\(\frac{11}{5} = \frac{22}{10}\)[/tex] (by multiplying both numerator and denominator by 2).
- Now add: [tex]\(\frac{22}{10} + \frac{3}{10} = \frac{22 + 3}{10} = \frac{25}{10}\)[/tex].
- Simplify [tex]\(\frac{25}{10}\)[/tex] to [tex]\(2.5\)[/tex].
So, [tex]\(2 \frac{1}{5} + \frac{3}{10} = 2.5\)[/tex].
#### (ii) [tex]\(\frac{7}{8} \times \frac{2}{3} - \frac{1}{4}\)[/tex]
1. Multiply [tex]\(\frac{7}{8}\)[/tex] by [tex]\(\frac{2}{3}\)[/tex].
- [tex]\(\frac{7}{8} \times \frac{2}{3} = \frac{7 \times 2}{8 \times 3} = \frac{14}{24}\)[/tex].
- Simplify [tex]\(\frac{14}{24}\)[/tex]:
- The greatest common divisor (GCD) of 14 and 24 is 2.
- [tex]\(\frac{14}{24} = \frac{7}{12}\)[/tex] when divided by GCD.
2. Subtract [tex]\(\frac{1}{4}\)[/tex] from [tex]\(\frac{7}{12}\)[/tex].
- Convert [tex]\(\frac{1}{4}\)[/tex] to have a common denominator with [tex]\(\frac{7}{12}\)[/tex].
- [tex]\(\frac{1}{4} = \frac{3}{12}\)[/tex] (by multiplying both numerator and denominator by 3).
- Now subtract: [tex]\(\frac{7}{12} - \frac{3}{12} = \frac{7 - 3}{12} = \frac{4}{12}\)[/tex].
- Simplify [tex]\(\frac{4}{12}\)[/tex]:
- The GCD of 4 and 12 is 4.
- [tex]\(\frac{4}{12} = \frac{1}{3}\)[/tex].
So, [tex]\(\frac{7}{8} \times \frac{2}{3} - \frac{1}{4} = 0.33333333333333337\)[/tex] (or [tex]\(\frac{1}{3}\)[/tex] approximately).
### Summary
1. (i) [tex]\(-1 + 3 - 6 = -4\)[/tex]
(ii) [tex]\(-4 + (2 \times -3) = -10\)[/tex]
2. (i) [tex]\(2 \frac{1}{5} + \frac{3}{10} = 2.5\)[/tex]
(ii) [tex]\(\frac{7}{8} \times \frac{2}{3} - \frac{1}{4} = 0.33333333333333337\)[/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.